2018
DOI: 10.1136/bmjsrh-2017-101928
|View full text |Cite
|
Sign up to set email alerts
|

Initiating intramuscular depot medroxyprogesterone acetate 24–48 hours after mifepristone administration does not affect success of early medical abortion

Abstract: Women choosing IM DMPA after EMA can be reassured that IM DMPA can be safely initiated at the time of misoprostol administration 24-48 hours after mifepristone without an increase in the risk of a continuing pregnancy. Both increasing gestation and previous termination were factors associated with an increased likelihood of continuing pregnancy following an EMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Although insertion of a POC implant at the time of mifepristone administration does not impair the efficacy of early medical abortion, administration of DMPA with mifepristone increased the risk of failed medical abortion (ongoing pregnancy) compared with DMPA administration delayed until after the abortion (3.5% vs 0.9%) . A recent study suggested that giving DMPA at the time of misoprostol administration had no effect on ongoing pregnancy rates . A recent randomized controlled trial demonstrated an increased risk of partial expulsion with fast‐track (≤3 days) insertion of the LNG‐IUS compared with insertion 2‐4 weeks after misoprostol administration (expulsion rates 12‐28 vs. 2%‐4%) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although insertion of a POC implant at the time of mifepristone administration does not impair the efficacy of early medical abortion, administration of DMPA with mifepristone increased the risk of failed medical abortion (ongoing pregnancy) compared with DMPA administration delayed until after the abortion (3.5% vs 0.9%) . A recent study suggested that giving DMPA at the time of misoprostol administration had no effect on ongoing pregnancy rates . A recent randomized controlled trial demonstrated an increased risk of partial expulsion with fast‐track (≤3 days) insertion of the LNG‐IUS compared with insertion 2‐4 weeks after misoprostol administration (expulsion rates 12‐28 vs. 2%‐4%) .…”
Section: Methodsmentioning
confidence: 99%
“…33 A recent study suggested that giving DMPA at the time of misoprostol administration had no effect on ongoing pregnancy rates. 34 A recent randomized controlled trial demonstrated an increased risk of partial expulsion with fast-track (≤3 days) insertion of the LNG-IUS compared with insertion 2-4 weeks after misoprostol administration (expulsion rates 12-28 vs. 2%-4%). 30,35 However, use of LNG-IUS was higher and pregnancy rates were lower at 1 year if the device had been inserted immediately.…”
Section: Contraception After Induced Abortionmentioning
confidence: 99%
“…1 ). A total of 16 studies met inclusion criteria: 9 focused on medical abortion and 7 on surgical abortion ( Tables 2 and 3 ) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . We did not identify any studies of hormonal contraception use following spontaneous or septic abortion that met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A fair-quality retrospective cohort study included 5122 people at ≤63 days who either initiated a hormonal method (DMPA, COC, POP, or implant) at the time of misoprostol or had no hormonal method. The 2-week follow-up involved a home low-sensitivity UPT [31] . For all 4 methods, there were no differences in continuing pregnancy rates compared with no hormonal method.…”
Section: Hormonal Contraception Vs Nonhormonal or No Contraceptionmentioning
confidence: 99%
“…Because mifepristone is a progesterone antagonist, there has been some concern that offering progestin-only methods (like progestin-only implants or injectables) at the time medication abortion drugs are taken might interfere with the effectiveness of medication abortion. This analysis from Lang and colleagues1 provides information from a large number of women who received a progestin-only injectable (depo medroxyprogesterone acetate, DMPA) at the time they received misoprostol (the second drug in the regimen, taken 24–48 hours after mifepristone). The findings are an important addition to the literature and add to the existing data that support providing contraception based on women’s choice and convenience.…”
mentioning
confidence: 99%